ISU FATHERLESSM DALAM FENOMENA BULLYING : TINJAUAN HUKUM KELUARGA ISLAM - Urfan Hilmi; Deni Maulani Hidayat (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2025)
The fatherless phenomenon (the absence of a father’s role) has become one of the major social issues influencing adolescent development. In Indonesia, the increasing cases of bullying in schools and communities are often linked to the weakening of the father figure’s role within the family. This article aims to examine the relationship between the fatherless phenomenon and adolescent bullying behavior, as well as to explore how Islamic family law can offer solutions to this issue. The research employs a qualitative approach through a literature study of the Qur’an, Hadith, and scholarly views regarding the father’s role in the family. The findings reveal that Islam positions the father as a leader, protector, and primary educator within the family (qawwam). The absence of this role creates emotional and moral voids in children, which may manifest as aggressive behaviors such as bullying. Therefore, strengthening the values of Islamic family law through family education and paternal role modeling serves as a preventive solution to this phenomenon